KEPEMIMPINAN PENDIDIKAN SEBAGAI KUNCI KEBERHASILAN STRATEGI MANAJEMEN KEARSIPAN - Agustin Puji Kurniasih; Nada Aliya Ramadhani; Nadia Arifa Ardiyunsyah; Zahra Dwi Anggraeni; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information technology in the digital age requires educational institutions to manage information quickly, appropriately, and accurately, one of which is through records management. However, in practice, records management in educational institutions still faces various challenges, such as unstructured systems, low utilization of technology, and limited human resource competencies. This study aims to analyze educational leadership strategies in improving the effectiveness of records management in educational institutions. The method used is a qualitative approach with a literature review, utilizing secondary data sourced from books, scientific journals, and relevant official documents. Data collection was conducted through literature review and selection, while data analysis employed content analysis by grouping and synthesizing information based on the research themes. The study findings indicate that leadership plays a strategic role in the success of records management. Indicators of effective leadership include analytical ability, communication skills, decisiveness, active listening, and assertiveness. The implementation of these leadership strategies can foster the creation of a systematic, efficient, and technology-based records management system. Thus, effective educational leadership is key to improving the quality of records management and supporting more optimal governance of educational institutions. Keywords: Educational Leadership, Records Management, Leadership Strategies, Literature Review